Comment: legal liability as climate change policy - Hilary Sigman (Rutgers University, Department of Economics, 2007)
Several U.S. states have attempted to use of legal liability imposed on greenhouse gas emitters as a public policy instrument for climate change. This brief comment considers the desirability of this approach, focusing on three possible roles for climate change liability: as a source of compensation, as a direct influence on greenhouse gas concentrations, and as a means to facilitate the adoption of ex ante public policies to control greenhouse gases. The strongest argument for liability may be that the threat of liability improves the chances that climate change policies will use more efficient, revenue-raising instruments.
Keywords: K32; 330; Environmental policy; law and economics; revenue recycling